Front Cover: A Universal DNA Aptamer that Recognizes Spike Proteins of Diverse SARS‐CoV‐2 Variants of Concern (Chem. Eur. J. 15/2022). Issue 15 (25th February 2022) - Zhang, Zijie; Li, Jiuxing; Gu, Jimmy; Amini, Ryan; Stacey, Hannah D.; Ang, Jann C.; White, Dawn; Filipe, Carlos D. M.; Mossman, Karen; Miller, Matthew S.; Salena, Bruno J.; Yamamura, Deborah; et al.
Abstract : A unique DNA aptamer, denoted MSA52, displays universally high affinity for the spike proteins of the wild‐type SARS‐CoV‐2 as well as its Alpha, Beta, Gamma, Epsilon, Kappa, Delta and Omicron variants. This aptamer also recognizes pseudotyped lentiviruses expressing eight different spike proteins of SARS‐CoV‐2 with very high affinity, exhibiting dissociation constants ( K d ) of 20–50 pM for these viruses. More information can be found in the Research Article by J. D. Brennan, Y. Li et al. (DOI: 10.1002/chem.202200078 ).